Peran Pendidikan Karakter Dalam Menghadapi Era Digital - Muchtar, Farah Firdausa; Rahman, Mita Chairunnisa; Azhar, Muthia Nur; Kamila Ishaq, Sehnaz Safana; Wahyudin, Dede; Caturiasari, Jennyta (FKIP, PGSD, Universitas Slamet Riyadi, 2024)
Character education in this digital era is quite a spotlight in the world of education. The purpose of this research is to examine and understand the